Peranan Jargon pada Iklan Minuman Ringan Teh Botol Sosro - Syahkuan, Jhonny; Nimah, Syarifah; Abdul Azis, Malik; Aminudin Bakri, Asman; Mochhamad Ulil Absor, Sayid (Jurnal Indonesia Sosial Sains, 2022)
Jargon is a special thing that can be used in a limited way in the field of knowledge or certain circles where they themselves know what it means and what it means. An ad editorial is certainly required not to use unique or difficult to understand words in making jargon. The purpose of the study was to determine the role of Jargon in the advertisement for soft drink tea Botol Sosro which reads "Whatever the food, drink it, Botol Sosro tea" and can also describe the role of Jargon in advertisements. This research uses descriptive quantitative method. The object of research is in the form of jargon in soft drink advertisements. The data examined in the study were in the form of soft drink advertising discourse. The primary data source in the study was soft drink advertisements. The results showed that the use of jargon by the surrounding community in various circles regardless of age and class included the use of language, form, and function of jargon. So it can be concluded that the unique advertising jargon for Teh Botol Sosro products is indeed very legendary, brand awareness is very high, people remember the product the most, and there is not a single community who does not know the buzz of the Teh Botol Sosro jargon.